2022
DOI: 10.33200/ijcer.596406
|View full text |Cite
|
Sign up to set email alerts
|

The Views of ELT Pre-Service Teachers on Using Drama in Teaching English and on Their Practices Involved in Drama Course

Abstract: The Views of ELT pre-service teachers on using drama in teaching English and on their practices involved in drama course.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 44 publications
1
3
0
Order By: Relevance
“…The most prominent codes associated with the cognitive domain was, "developing the creative thinking skills", "providing the opportunity for being creative and original", "providing the development of verbal skills", "providing support to generate new ideas" "providing permanent learning", and "gaining the habit of asking questions". These emergent codes showed the consistency with the literature regarding the effects of drama on the cognitive domain in terms of developing creative thinking skills (Baykal, Sayın & Zeybek, 2019;Can Yaşar & Aral, 2012;Demir, 2019;Dönük, 2018;Freeman, Sullivan & Fulton, 2003;Moore & Russ, 2008; The most striking codes regarding the social domain were "improving relationships with friends" "providing opportunities to form groups", "providing opportunities to develop social skills", "increasing social integration", and "providing participants to express themselves comfortably". Similarly, in Kelly"s (2006) study, the author observed the positive impact of groupings on the students" experience in drama.…”
Section: Discussionsupporting
confidence: 68%
“…The most prominent codes associated with the cognitive domain was, "developing the creative thinking skills", "providing the opportunity for being creative and original", "providing the development of verbal skills", "providing support to generate new ideas" "providing permanent learning", and "gaining the habit of asking questions". These emergent codes showed the consistency with the literature regarding the effects of drama on the cognitive domain in terms of developing creative thinking skills (Baykal, Sayın & Zeybek, 2019;Can Yaşar & Aral, 2012;Demir, 2019;Dönük, 2018;Freeman, Sullivan & Fulton, 2003;Moore & Russ, 2008; The most striking codes regarding the social domain were "improving relationships with friends" "providing opportunities to form groups", "providing opportunities to develop social skills", "increasing social integration", and "providing participants to express themselves comfortably". Similarly, in Kelly"s (2006) study, the author observed the positive impact of groupings on the students" experience in drama.…”
Section: Discussionsupporting
confidence: 68%
“…Earlier research highlighted that process drama provides learners with real-life context practice, making language learning more relevant and meaningful (Baldwin & Galazka, 2021). Studies have shown that process drama improves speaking ability (Bsharat & Brahmeh, 2020), enhances listening comprehension and vocabulary acquisition (Shahani & Tahriri, 2015), and develops reading and writing skills (Baykal et al 2019;Alasmari & Alshae'el, 2020;Rieg & Paquette, 2009). Drama-based instruction can significantly enhance speaking skills in English as a Foreign Language (EFL) learners (Sirisrimangkorn, 2018) and provide a platform for students to engage in authentic contexts (Liu et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Shahani and Tahriri (2015) found that process drama enhanced the listening comprehension and vocabulary acquisition of EFL learners by exposing them to different types of texts and genres. Process drama can also develop learners' reading and writing skills by integrating them with other language skills and encouraging learners to create and respond to texts in various forms and modes (Baykal et al 2019;Alasmari & Alshae'el, 2020;Rieg & Paquette, 2009). Drama plays a crucial role in education by providing learners with the opportunity to immerse themselves in a fictional world, enabling them to engage in authentic and meaningful ways of exploration and communication.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, especially in Turkey, several studies have been conducted with pre-service teachers in relation to drama-based methods. Baykal, Saym and Zeybek (2019) report that English language pre-service teachers in Turkey found a course in using drama valuable, had mainly positive views of using drama in language teaching, and anticipated using drama in their own teaching. Doğan and Cephe (2018) found that student teachers in a 30-hour creative drama workshop, part of an English language training program, improved their teaching skills, and had very positive perceptions of using drama in language teaching.…”
Section: Using Drama-or Other Action-based Methods In Language Educationmentioning
confidence: 99%